HEMOPOIETIC SENSITIVITY OF THE RATS TO RADIATIVE EFFECT IN ANTENATAL ONTOGENESIS - Romanova, E.A.; Sidorenko, T.A.; Igumnova, N.I.; Gogadze, L.G. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
Morphologic and cytogenetic variations of hemopoesis of rats by influence antenatal radiation was studied. Cellular composition of bone marrow of antenataly irradiated animals testify about expressed disbalance of the production, maturation and differentiation of hemopoietic cells in the all hemopoetic sprouts. It was found the increase of cells with chromosomal aberrations among the irradiated posteritys myelocariocytes.